Yonatan Ratosh's "Cultural Entrepreneurship" and the Invention of "Hebrew" Nationalism. Issue 3 (1st December 2019) - Giladi, Amotz
Abstract : Israeli poet Yonatan Ratosh was the leader of the Young Hebrews, a nationalist group active from the 1940s to the 1970s. Despite his opposition to Zionism and his aspiration to revive the ancient Hebrews' premonotheistic civilization, Ratosh shared Zionism's ambition to elaborate a new Israeli identity. One prominent act of this mission involved enlarging the literary corpus in Hebrew through translation. Although initially a means of income, for Ratosh translation increasingly came to be a way to express his ideological position and his self-image as an intellectual. Thus, Ratosh provides an example of how developing a national identity can coincide with appropriating foreign literature. With his regular exhortations that Hebrew readers attain knowledge of foreign cultures, Ratosh did not intend to promote cosmopolitanism. Rather, he considered these endeavors as ultimately reinforcing a "Hebrew" identity.